Enhanced palm oil mill effluent treatment and biomethane production by co-digestion of oil palm empty fruit bunches with Chlorella Sp - Ahmad, A. (Wiley-Liss Inc., 2014)
Palm oil mill effluent (POME) has high chemical oxygen demand (COD) and biological oxygen demand (BOD) and minerals such as nitrogen and phosphorous which can cause severe pollution to the environment and water resources. In this study, aerobic and anaerobic co-digestion of oil palm empty fruit bunches (OPEFB) with Chlorella sp. was developed for POME treatment and biomethane production. Higher removal efficiency (56-98) of COD, BOD, TOC, and TN after 3 and 7 days' treatment were achieved with microalgae than without microalgae. Using response surface methodology, the highest specific biogas production rate (0.128-0.129m3/kgCOD/day) and biomethane yield (5256.8-5295.8mL/L POME/day) were achieved with Chlorella sp. at 2mL/mL POME, and OPEFB at 0.12g/mL POME. Without both microalgae and OPEFB, the methane yield was 1.4-fold lower. The values for optimum conditions were predicted well by the model within 5 error. Â© 2014 Canadian Society for Chemical Engineering.